Desvelando para ressignificar: processos educativos decorrentes de uma práxis musical dialógica intercultural - Martins, Denise Andrade de Freitas (2015)
The aim of this study was to identify and understand the educational processes originated from the construction-reconstruction of an intercultural dialogical musical practice together with a participating community (students, parents, educators) from an extension project, in the city of Ituiutaba, Minas Gerais, the Project Writing the Future (Re) cutting papera, creating pannels. This project, which involves three educational institutions: the University, Universidade do Estado de Minas Gerais, Unidade Ituiutaba, the Music School, Conservatório Estadual de Música Dr. José Zóccoli de Andrade , and the Basic Educational School, Escola Estadual Governador Bias Fortes, is understood as a social practice, given that everybody participates freely, being able to access or leave when they wish to do so. Based on the dialogue and marked by a strong sense of collaboration, companionship is a basic requirement for such practice. The processo of construction-reconstruction of the research had as reference the pedagogical principles of the Brazilian educator Paulo Freire and was composed of two moments: data collection (intervention procedures: questionnaires, interviews, meetings) and development (gatherings, partitura, travelling, performance) of the Generating Music, seen as the step by step of this process, based on the daily lives of the people involved their musical tastes, knowledge and skills. The theoretical reference was basically sustained mainly by the concepts of culture and interculturality. Inspire by phenomenology and of a qualitative nature, the principal tool for data collection was the field journals, with a later analysis, also interviews, photographs, film footages, drawings and texts written by the collaborating participants, term used in this research to refer to the students. The analysis of the data collected during the intervention and registered in the field journals enabled the construction of the following categories: A) Strengthening of the Identity: Oh my, he is strong, he is Zumbi, black warrior just like us! ; B) Respect towards others: I was feeling rather comfortable to play some music! ; C) Desire to become more: When this project started it changed my whole life! [...]. Now I can only do music! . Thus, we consider that practices in Musical Education demand, from those involved in it, commitment and responsability, permanent search of knowledge and skills, respect and acknowledgement of others. However, the process of teachers development, the stimulus of motivation with musical and personal development quality, the c reative and cooperative interaction in the familiarity of the different cultures, the guarantee of a musical education and teaching commited to the development of citizenship and the rights exercise, yet, present themselves as challenges to be face at present.